The Impact of Gamification on Gen Z’s Behavioral Intention through ECommerce Shopee: Does Reward Moderate the Relationship? - Joe Eklesia Apostolos Sujarwo; Cynthia Anna Wijayanti (Universitas Pelita Harapan, 2024)
This study explores the impact of gamification on the behavioral intention of Generation Z users within the Indonesian Shopee e commerce platform, examining rewards as a moderating factor. Using the Technology Acceptance Model (TAM) framework, the research analyzes how perceived enjoyment, usefulness, ease of use, and social interaction influence users’ intentions to engage with gamified features. Data from 178 respondents were analyzed via Structural Equation Modeling (SEM) using SmartPLS. Findings indicate that gamification positively affects perceived enjoyment, usefulness, ease of use, and social interaction, enhancing behavioral intention. However, rewards as a moderating factor did not significantly impact these relationships. The study emphasizes gamification's role in boosting engagement on digital platforms among Generation Z consumers, though the role of rewards in moderating this effect may vary. This research contributes to understanding how gamified elements enhance user engagement and loyalty on e-commerce platforms.